1998
DOI: 10.1074/jbc.273.50.33184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Saccharomyces cerevisiae Δ3,Δ2-Enoyl-CoA Isomerase

Abstract: We report here the identification of the Saccharomyces cerevisiae peroxisomal ⌬ 3 ,⌬ 2 -enoyl-CoA isomerase, an enzyme that is essential for the ␤-oxidation of unsaturated fatty acids. The yeast gene YLR284C was identified in an in silico screen for genes that contain an oleate response element, a transcription factor-binding site common to most fatty acid-induced genes. Growth on oleic acid resulted in a significant increase in YLR284C mRNA, demonstrating that it is indeed an oleate-induced gene. The deduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 41 publications
0
65
1
Order By: Relevance
“…Both sets of primers append BamHI and NotI sites (underlined) to the 5Ј-and 3Ј-ends of the HAOX1 ORF, respectively. The PCR product from each reaction was digested with BamHI and NotI and cloned between the BamHI and NotI sites of pMBP (27), a modified form of the pMALc2 expression vector (New England Biolabs) to make pMBP-HAOX1 and pMBP-HAOX1⌬KI, respectively. The HAOX1 ORF was excised from pMBP-HAOX1 and inserted between the BamHI and NotI sites of pcDNA3-Nmyc (28), a mammalian expression vector designed to express proteins in fusion with an amino-terminal c-myc epitope, creating pcDNA3-Nmyc/HAOX1.…”
Section: Methodsmentioning
confidence: 99%
“…Both sets of primers append BamHI and NotI sites (underlined) to the 5Ј-and 3Ј-ends of the HAOX1 ORF, respectively. The PCR product from each reaction was digested with BamHI and NotI and cloned between the BamHI and NotI sites of pMBP (27), a modified form of the pMALc2 expression vector (New England Biolabs) to make pMBP-HAOX1 and pMBP-HAOX1⌬KI, respectively. The HAOX1 ORF was excised from pMBP-HAOX1 and inserted between the BamHI and NotI sites of pcDNA3-Nmyc (28), a mammalian expression vector designed to express proteins in fusion with an amino-terminal c-myc epitope, creating pcDNA3-Nmyc/HAOX1.…”
Section: Methodsmentioning
confidence: 99%
“…All polymerase chain reactions were performed with a low error-rate mixture of polymerases (Expand, Roche Molecular Biochemicals). The polymerase chain reaction product from each reaction was digested with SalI and NotI and subcloned into the SalI and NotI sites of pMBP (7,16). The sequence of each form of the human PECI ORF in pMBP was confirmed by automated fluorescent sequencing, and the resulting plasmids were denoted pMBP-PECI and pMBP-PECI⌬SKL.…”
Section: Cdna Cloning Of Mammalian Eci1pmentioning
confidence: 99%
“…However, we and others have recently identified and characterized the S. cerevisiae ⌬ 3 ,⌬ 2 -enoyl-CoA isomerase (7,8) and have found that this enzyme, Eci1p, shares few primary sequence features with MFE1. In this report we describe the identification and characterization of a novel, ubiquitously expressed mammalian peroxisomal ⌬ 3 ,⌬ 2 -enoyl-CoA isomerase (PECI) that is homologous to yeast Eci1p.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic and peroxisomal NADP-dependent isocitrate dehydrogenases might function in a shuttle in a manner similar to the malate dehydrogenases. The goal is different, however -to keep the intraperoxisomal pool of NADP reduced [12][13][14] . This results in the simultaneous flow of reduction equivalents in opposite directions, which are kept separated by different cofactors (NAD/NADP) and substrates (malate/citrate).…”
Section: Peroxisome Metabolismmentioning
confidence: 99%